Court System Transformation; Maximizing Electronic Courts through the Implementation of Swift, Simple, and Cost Effective Principles - Sujatmiko, Bagus; Rato, Dominikus; Anggono, Bayu Dwi (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2023)
Nowadays the world has often labeled as the 4.0 era, humans can reach almost everything at the snap of a finger. The development of information technology has penetrated all lines of life, including the law enforcement. The judiciary system as the main forum for the law enforcement process is also have to adapt, if not to do so, the judiciary system may be deemed as a failed system. The enactment of Supreme Court Regulation Number 1 of 2009 became the sign of electronic litigation era in Indonesia. However, long before that the Supreme Court has already improved the judiciary system electronically, because “judiciary system” not only means the litigation process but other process includes the case administration. Writer in this paper will discuss on what are the improvements that Supreme Court have made on judiciary system and further to analyze normatively on whether such improvement may support the fulfillment of judiciary principle especially the principle of fast, simple and low-cost proceeding, or otherwise whether such improvement only bring other problems into the existing system.